Effect of Virgin Coconut Oil Supplementation on Obese Rats’ Anthropometrical Parameters and Gut Bacteroidetes and Firmicutes Change Ratio - Ahnan, Amadeus Driando; Agustinah, Widya (International Coconut Community Journal, 2016)
Previous clinical trials using virgin coconut oil (VCO) showed a potential anti-obesity effect, including for human, by reducing the waist circumference. However, there was not discovered any research that examined its anti-obesity effect in relation with gut microbiota parameters as one of current approaches of obesity parameters, for example Firmicutes and Bacteroidetes. This research was conducted to examine the effect of VCO supplementation on the change of Firmicutes and Bacteroidetes in comparison to the anthropometrical parameters. The experiment was done using 14 days obese-induced female Sprague-Dawley rats supplemented with 0.01% w/w and 0.02% w/w VCO for 28 days. The anthropometric data collection consisted of body weight (BW), body mass index (BMI), abdominal circumference (AC), and body length (BL). Ratio changes in –fold increase between Day 28 and Day 0 of Bacteroidetes and Firmicutes were retrieved by using relative quantification normalized against unit mass calculation, using the cycle threshold values from real-time polymerase chain reaction (RT-PCR) method with SYBR Green fluorescence and standard curve derived from tenfold 5 points dilution series of recombinant plasmid for efficiency calculation. VCO supplementation stimulated significant increase on anthropometric parameters on BW and AC (p<0.05), while insignificant changes were shown on Bacteroidetes and Firmicutes ratio with tendency of increasing and decreasing respectfully, with no significance. The result indicated that VCO supplementation in the given doses promoted pro-obesity effect on key anthropometric parameters, while showed potential anti-obesity effect on the gut microbiota parameter. Further researches were needed especially in determining the effective dose to promote the anti-obesity effect of VCO and revealing any possible cellular and molecular mechanisms.